Multiple objective optimization using artificial bee colony Algorithm for optimal placement and sizing of distributed generation - Nur Fairuz Mohd Johan (School of Electrical System Engineering, Universiti Malaysia Perlis, 2016)
The main objective of this research is to investigate the optimal placement and sizing of single and multiple DGs in distribution system using multi-objective method.